Study on active tectonic faults using soil radon gas method in Viet Nam - Xuan*, Pham Tich; Pho, Nguyen Van; Chinh, Vu Van; Dang, Pham Thanh; Lien, Nguyen Thi; Tra, Doan Thu; Nga, Hoang Tuyet; Quynh, Bui Van; Luan, Nguyen Van; Qua, Nguyen Xuan (Vietnam Journal of Earth Sciences, 2017)
This paper presents the results of soil radon gas measurement in three areas, including Thac Ba and Song Tranh 2 hydropower plants, and the planned locations of the nuclear power plants Ninh Thuan 1&2 using solid-state nuclear track detectors (SSNTD) with the aim of clarifying the activity of tectonic faults in these areas. The activity of tectonic faults was assessed through radon activity index KRn (the ratio between anomaly and threshold), which was divided into 5 levels as follows ultra-high (KRn> 10), high (10≥KRn> 5), high (5≥KRn> 3), medium (3≥KRn> 2) and low (KRn≤2). Soil radon gas measurement results showed that in the radon gas concentrations in the Thac Ba hydropower plant area ranged from 72 Bq/m3 to 273.133 Bq/m3 and maximum radon activity index KRn reached 9.75 (high level). High KRn indexes show Chay River fault active in recent time and the sub-meridian distribution of Rn anomalies suggested a right-slip motion of the fault. Rn concentrations in the Ninh Thuan 1&2 areas ranged from 6 Bq/m3 to 52.627 Bq/m3, however, the KRn indexes were mostly low (KRn≤3) and the highest value was only 3.42, suggesting that expression of activity of the tectonic faults in this region is not clear, even no expression of fault activity. In the Song Tranh 2 hydropower plant and adjacent areas, radon concentrations ranged from 29 Bq/m3 to 77.729 Bq/m3 and maximum KRn index was 20.16 (ultra-high level). The faults having clearer activity expression are Hung Nhuong - Ta Vy, Song Tra Bong and some high order faults, especially the northwest - southeast segments of these faults or their intersections with the northwest - southeast faults. In addition, the high values KRn in the mentioned intersections can be evidenced for the activeness of northwest - southeast faults at the present time. The studies on active faults using soil radon gas method were performed in areas with very different geological and structural features, but the results are well consistent with the results of previous investigations obtained by other methods. It confirmed the effectiveness and capability of soil radon gas geochemistry applying to study active tectonic faults. References Al-Hilal M., Al-Ali A., 2010. The role of soil gas radon survey in exploring unknown subsurface faults at Afamia B dam, Syria. Radiat. Meas, 45, 219-224. Amponsah, P., Banoeng-Yakubo, B., Andam, A., Asiedu, D., 2008. Soil radon concentration along fault systems in parts of south eastern Ghana. J. Afr. Earth Sci. 51, 39-48. Asumadu-Sakyi A.B., Fletcher J.J., Oppon O.C., Qua- shie F.K., Wordson D.A., Adjei C.A., Amartey E.O., Darko E.O. and Amponsah P., 2011. Preliminary Studies on Geological Fault Location Using Solid State Nuclear Track Detection. Research Journal of Environmental and Earth Sciences, 3(1), 24-31. Baubron, J.-C., Rigo, A., Toutain, J.-P., 2002. Soil gas profiles as a tool to characterize active tectonic are- as: the Jaut Pass example (Pyrenees, France). Earth Planet. Sci. Lett, 196, 69-81. Burton, M., Neri, M., Condarelli, D., 2004. High spatial resolution radon measurements reveal hidden active faults on Mt. Etna. Geophys. Res. Lett, 31, L07618. Ciotoli, G., Etiope, G., Guerra, M. & Lombardi, S., 1999. The detection of concealed faults in the Ofan- to basin using the correlation between soil gas fracture surveys. Tectonophysics, 299(3-4), 321-332. Ciotoli, G., Lombardi, S. & Annunziatellis, A., 2007. Geostatistical analysis of soil gas data in a high seismic intermontane basin: Fucino Plain, central Italy. J. Geophys. Res., 112, B05407, doi:10.1029/2005JB004044. Font, L., Baixeras, C., Moreno, V., Bach, J., 2008. Soil radon levels across the Amer fault. Radiat. Meas, 43, 319-323. Geological and Mineral Resources Map of Viet Nam on 1:200,000, 2005. Published by Department of Geology and Minerals of Viet Nam, Ha Noi, Lists: Yen Bai (F-48-XXI), Tuyen Quang (F-48-XXII), Quang Ngai (D-49-VII&VIII), Hoi An (D-49-I), Da Lat - Cam Ranh (C-49-I&II). Ghosh D., Deb A. and Sengupta R., 2009. Anomalous radon emission as precursor of earthquake. J. Appl. Geophys., 69, 67-81. González-Díez, A., Soto, J., Gómez-Arozamena, J., Bonachea, J., Martínez-Díaz, J.J., Cuesta, J.A.,Olague, I., Remondo, J., Fernández Maroto, G., Díaz de Terán, J.R., 2009. Identification of latent faults using a radon test. Geomorphology, 110,11‐19. Haerudin N, Wahyudi, Munadi S., Suryanto W., 2013. A Soil Gas Radon Survey to Determine Fault at Southern Part of Rajabasa Geothermal Field, Lampung Indonesia. International Journal of Engineering & Technology IJET-IJENS, 13(1), 75-81. Hauksson E., 1981. Radon content of groundwater as an earthquake precursor: evaluation of worldwide data and physical basis. J. Geophys. Res., 86, 9397-9410. Ioannides, K., Papachristodoulou, C., Stamoulis, K., Ka- ramanis, D., Pavlides, S., Chatzipetros, A., Karakala, E., 2003. Soil gas radon: a tool for exploring active fault zones. Appl. Radiat. Isot, 59, 205-213. Israel H. and Bjornsson S., 1967. Radon (Rn-222) and thoron (Rn-220) in soil air over faults. Z. Geophys, 33, 48-64. Kemski, J., Siehl, A., Stegemann, R., Valdivia- Manchego, M., 2001. Mapping the geogenic radon potential in Germany. Sci. Total Environ, 272, 217-230. King C.Y., 1978. Radon emanation on San Andreas fault. Nature, 271, 516-519. King, C.Y., King, B.S., Evans, W.C., 1996. Spatial radon anomalies on active faults in California. Appl. Geochem, 11, 497-510. Laskar I., Phukon P., Goswami A.K., Chetry G. and Roy U.C., 2011. A possible link between radon anomaly and earthquake. Geochemical Journal, 45, 439-446. Lombardi, S., Voltattorni, N., 2010. Rn, He and CO2 soil gas geochemistry for the study of active and inactive faults. Appl. Geochem, 25, 1206-1220. Moussa M.M., Arabi A-G. M. E., 2003. Soil radon survey for tracing active fault: a case study along Qena- Safaga road, East Desert, Egypt. Radiat. Meas, 37,211-216. Papastefanou C., 2010. Variation of radon flux along active fault zones in association with earthquake occurrence. Radiat. Meas, 45, 943-951. Nguyen Dang Tuc, 2000. Kinematic characteristics of the Red River - Chay River fault zone in Cenozoic. Journal of Sciences of the Earth, 22, 174-180 (in Vietnamese). Nguyen Van Pho, Nguyen Trong Yem, 1996. Gas geochemical approach in study of the activity of Red River fault system. Journal of Geology, Ha Noi, series A, 236, 9-10. Nguyen Van Pho, Hoang Tuyet Nga, 1996. Some results of the micro geodynamic maping in Thac Ba area by using of nuclear track detector method. In Geology - Resources, Sci. and Tech. Publishing house, Ha Noi, , 187-191. Nguyen Van Pho, Hoang Thi Tuyet Nga, Doan Thi Thu Tra, 1999. Study on the stability of Thac Ba hy- drpopower dam by using nuclear track detector method. Journal of Geology, Ha Noi, Series B, 13-14, 270-271. Nguyen Van Pho, Hoang Thi Tuyet Nga, Nguyen Trung Minh, Doan Thi Thu Tra, Vu Manh Long, Le Thanh Chung, Nguyen Dinh Xuyen, Pham An Cuong, 2004. Results of radon continuous measurements in soil gas at the North-Western area. Journal of Sciences of the Earth, 26, 653-656 ( in Vietnamese). Nguyen Trong Yem, 1996. Regimes of tectonic stress field during Cenozoi in Vietnam. Journal of Geology, Ha Noi, series A, 236, 1-6. Reimann C., Filzmoser P., Garrett R.G., 2005. Background and threshold: critical comparison of methods of determination. Science of the Total Environment, 346, 1-3, 1-16. Richon P., Klinger Y., Tapponnier P., Li C.X., Van Der Woerd J., Perrier F., 2010. Measuring radon flux across active faults: Relevance of excavating and possibility of satellite. Radiation Measurements, 45, 211-218. Riggio A., and Santulin M., 2015. Earthquake forecasting: a review of radon as seismic precursor. Bollettino di Geofisica Teorica ed Applicata, 56(2), 95-114. Seminsky K.Zh., Demberel S., 2013. The first estimations of soil-radon activity near faults in Central Mongolia. Radiation Measurements, 49, 19-34. Swakón, J., Kozak, K., Paszkowski, M., Gradzinski, R., Loskiewicz, J., Mazur, J., Janik, M., Bogacz, J.,Horwacik, T., Olko, P., 2004. Radon concentration in soil gas around local disjunctive tectonic zones in the Krakow area. J. Environ. Radioact, 78, 137-149. Tanner, A.B., 1980. Radon migration in the ground: A supplementary review, in Gesell, T.F., and Lowder, W.M., eds., Natural Radiation Environment III: U.S. Dept. Energy Rept. CONF-780422, 1, 5-56. Toutain J.P., Baubron J.C., 1999. Gas geochemistry and seismotectonics: a review. Tectonophysics 304, 1-27. Tran Trong Hue, 1996. First results of research present geodynamics by soil gas radon method. In Geology - Resource, Ha Noi, 1, 179-185. Tran Trong Hue, 1999. Characteristics of radon radioactive gas in Song Ma fault zone. Journal of Sciences of the Earth, 123-128. Tung S., Leung J. K. C., Jiao J. J., Wiegand J., Wartenberg W., 2013. Assessment of soil radon potential in Hong Kong, China, using a 10-point evaluation system. Environmental Earth Sciences, 68(3), 679-689. Tran Van Duong, Tran Trong Hue, 1996. Some results of the investigation active faults in the South Central Viet Nam by radon method. Journal of Science of the Earth, 18, 276-288. Tran Van Tri, Vu Khuc et al., 2009. Geology and earth resources of Viet Nam. Publishing House for Science and Technology, Ha Noi, 645. Utkin V.I., Yurkov A.K., 2010. Radon as a tracer of tectonic movements. Russian Geology and Geophysics, 51, 220-227. Wakita H., Nakamura Y., Notsu K., Noguchi M. and Asada T., 1980. Radon anomaly: a possible precursor of the 1978 Izu-Oshimakinkai earthquake. Sci., 207, 882-883. Walia V., Mahajan S., Kumar A., Singh S., Singh Bajwa B., Dhar S., Yang T.F., 2008. Fault delineation study using soil gas method in the Dharamsala area, NW Himalayas, India . Radiat. Meas, 43, 337-342. Wang X., Li Y., Du J., Zhou X., 2014. Correlations be- tween radon in soil gas and the activity of seismo- genic faults in the Tangshan area, North China. Ra- diation Measurements, 60, 8-14.